Stock market participation in less developed countries: a perception-based evidence from Uganda - Zainabu Tumwebaze; Laura Orobia; Juma Bananuka; Caroline Bonareri Tirisa; Aminah Balunywa (Cogent Business & Management, 2022)
This study aims to examine the contribution of participation costs (floatation costs, compliance costs and marketing costs) to stock market participation using evidence from Uganda-a developing country. Using a cross-sectional and correlational research design, data were collected through a questionnaire survey of 219 small and medium enterprises. We used correlation coefficients and linear regression to test our hypotheses. The hierarchical regression analysis results suggest that participation costs such as floatation costs, compliance costs, and marketing costs are significant predictors of stock market participation while firm age and firm size (control variables) are non-significant. The study uses a cross-sectional research design. The major weakness with cross-sectional research designs is that, it is difficult to monitor changes in behavior over time. To the practitioners and policymakers, this study suggests that the Ugandan Capital Market Authority should review the costs (floatation costs, compliance costs, and marketing costs) involved in accessing finance through the stock exchange. This will go a long way in making the stock market an alternative financing option, especially in this era of rising costs of capital provided by other financial intermediaries. The study examines the behavior of the elements of participation costs in explaining stock market participation, an aspect that has not been adequately highlighted in previous studies. Results indicate that among elements of participation costs, floatation costs are more significant, followed by compliance costs. Market costs turnout to be the least participation cost in explaining stock market participation.
Keywords: 650; Uganda; compliance costs; floatation costs; marketing costs; Stock market participation